Clean energy technology pathways from research to commercialization: Policy and practice case studies - Engel-Cox, Jill A.; Merrill, Wyatt G.; Mapes, Marie K.; McKenney, Ben C.; Bouza, Antonio M.; DeMeo, Edgar; Hubbard, Mary; Miller, Eric L.; Tusing, Richard; Walker, Brian J. (Frontiers in Energy Research, 2022)
Clean energy research and development (R&D) leading to commercial technologies is vital to economic development, technology competitiveness, and reduced environmental impact. Over the past 30 years, such efforts have advanced technology performance and reduced cost by leveraging network effects and economies of scale. After demonstrating promise in applied R&D, successful clean energy and energy efficiency technologies are incorporated into an initial product sold by the private sector. Despite its importance, processes by which first commercialization occurs are difficult to generalize while capturing specific insights from practitioners in markets and technologies. This paper presents a policy-focused qualitative assessment of the first commercialization of four diverse energy technologies: thin film photovoltaics, wind turbine blades, dual-stage refrigeration evaporators, and fuel cells for material handling equipment. Each technology presents distinct value propositions, markets, and regulatory drivers. The case studies indicate three common characteristics of successful first commercialization for new energy technologies: (1) good fit between the technology, R&D infrastructure, and public-private partnership models; (2) high degree of alignment of government regulations and R&D priorities with market forces; and (3) compatibility between time scales required for R&D, product development, and opportunities. These findings may inform energy investment decision-making, maximize benefits from R&D, and advance the transition to a low-emission future.